Comparison of the Effectiveness of Blue Light Therapy as an Adjuvant Therapy with Topical Antibiotics in Acne Vulgaris Patients - Lubis, Raisa Alifia Mubarak; Batubara, Dian Erisyawanty (Universitas Muhammadiyah Sumatera Utara, 2026)
Abstract: Acne vulgaris, commonly known as acne, is one of the most common disorders of the skin due to disorders in the sebaceous glands or oil glands that are found on the skin. Management of acne vulgaris can be given in the form of antibiotics, accompanied by additional therapy to somewhat increase the effectiveness of healing. One of the additional therapies provided is Photodynamic Therapy (PDT). This study aims to compare the level of effectiveness of blue light therapy as an adjuvant therapy with topical antibiotics in acne vulgaris patients at the Faculty of Medicine, University of Muhammadiyah North Sumatra, Batch 2020, 2021, 2022 and 2023. This study involved 32 student subjects who had acne vulgaris. This study is an observational study with the prospective cohort method. Students who are indicated to have a severity level of 2 based on the Global Acne Grading System are given therapy. The collected data were processed with the Wilcoxon Test. The results showed a decrease in severity with topical antibiotics in as many as 7 people (20%) and topical antibiotics with photodynamic therapy in as many as 12 people (80%), with the highest gender distribution in women (72%). The results of the data test showed no significant relationship or difference between the two treatment groups. The conclusion of this study did not find a significant difference between the two treatment groups, but the number of samples that recovered in the group of topical antibiotics with additional therapy was much higher.